Prisonniers du Soleil. La part maudite de la modernité - Guillaume Désanges; Thomas Golsenne (Images Re-Vues)
Guillaume Désanges, art curator, is asked by Thomas Golsenne, art historian, to explain his understanding of ornament as modernism “dark side” and its analytical use by contemporary artists as Corey McCorkle or Isabelle Cornaro. A matter that he freely processed with his 2010 exhibition at Le Plateau in Paris, Prisonniers du soleil (Prisoners of the sun). Along this way, ornament appears to be central in a network of problems at stakes with some larger historical, epistemological, political and moral questions.